Congenital qualitative platelet disorders in children (report on 60 patients) - Hiçsönmez, Gönül (The Turkish Journal of Pediatrics, 1982)
Qualitative platelet disorders were shown to be the second most frequent cause of congenital bleeding diathesis, after hemophilia A, diagnosed at Hacettepe Children’s Hospital, Ankara, between 1974 and 1980. During this period, 60 new children with congenital qualitative platelet disorders who were seen because of mild, moderate or (rarely) severe hemorrhagic diathesis were evaluated. Thirty-seven of them were shown to have thrombasthenia, 11 thrombopathia, 9 Bernard-Soulier syndrome, and 3 Hermansky-Pudlak syndrome. The high incidence of qualitative platelet disorders in Turkey is most likely related to the high frequency of consanguineous marriages, especially in small villages.As a result of this study, we would like to emphasize the importance of considering congenital platelet disorders in the differential diagnosis of congenital bleeding diathesis when prothrombin and partial thromboplastin times are normal.
Keywords: congenital qualitative platelet diseases; platelet functional disorder; thrombopathia